Early events after infection of Escherichia coli by bacteriophage T5. Induction of a 5'-nucleotidase activity and excretion of free bases. - Warner, H R (1975)
Thymine-containing compounds, produced degradation of Escherichia coli DNA after infection of the cells with bacteriophage T5, did not accumulate in the cell but were excreted into the medium as the DNA was degraded. The ultimate degradation product was extracellular thymine that was not reutilized when T5 DNA synthesis began. This excretion of thymine may have been due in part to the induction of 5'-nucleotidase activity within 3 min after T5 infection. The level of this activity reached a maximum between 4 to 6 min after infection and then rapidly declined to its preinfection level by 10 to 15 min after infection. Chloramphenicol added before or soon after infection prevented the appearance of the nucleotidase. The induced nucleotidase activity was active not only on dTMP but also on dAMP, dGMP, and dCMP.